Bacteriuria and Urinary Retention following Gynaecological Surgery: Comparing Short vs Long Term Catheterization - Thapa, M; Shrestha, J; Pradhan, B N; Padhye, S M (Journal of Nepal Health Research Council, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Background: Post operative bladder drainage is important care following gynaecological surgeries. This study was done to compare the incidence of urinary retention and bacteriuria following long term versus short term catheterization. Methods: The patients who were admitted for gynaecological major surgeries were enrolled in this study. One group of patients had post operative indwelling catheterization for 24hrs (short term catheterization) and another group of patients had catheterization for more than 48 hrs (long term catheterization). The urine examination and culture sensitivity was sent for all patients at the removal of catheter. The patients were followed after removal of catheter for urinary retention. Results: Total of 102 patients were studied. There were 48 patients in short term catheterization group and 54 patients in long term catheterization group. In short term catheterization group, 3 (6.2%) cases had bacteriuria and no cases of urinary retention were observed. In prolonged catheterization group, 6 cases (11.1%) had bacteriuria and 2 cases (3.7%) had urinary retention. Conclusions: This study has concluded that short time catheterization following gynaecological surgery had fewer incidences of bacteriuria and urinary retention than long term catheterization. Key words: bacteriuria, catheterization, urinary retention.